Rigid bioplastics shape the microbial communities involved in the treatment of the organic fraction of municipal solid waste - Bandini, Francesca; Vaccari, Filippo; Soldano, Mariangela; Piccinini, Sergio; Misci, Chiara; Bellotti, Gabriele; Taskin, Eren; Cocconcelli, Pier Sandro; Puglisi, Edoardo (Frontiers in Microbiology, 2022)
While bioplastics are gaining wide interest in replacing conventional plastics, it is necessary to understand whether the treatment of the organic fraction of municipal solid waste (OFMSW) as end-of-life option is compatible with their biodegradation, but also their possible role in shaping the microbial communities involved in the processes. In the present work we assessed the microbiological impact of rigid polylactic acid (PLA) and starch-based bioplastics (SBB) spoons on the thermophilic anaerobic digestion and the aerobic composting of OFMSW under real plants conditions. In order to thoroughly evaluate the effect of PLA and SBB on the bacterial, archaeal and fungal communities during the process, high-throughput sequencing (HTS) technology was carried out. The results suggest that bioplastics shape the communities’ structure especially in the aerobic phase. Distinctive bacterial and fungal sequences were found for bioplastics compared to the positive control, which showed a more limited diversity. Mucor racemosus was especially abundant in composts from bioplastics’ treatment, whereas Penicillium roqueforti was found only in compost from PLA and Thermomyces lanuginosus in that from SBB. Further studies are needed to better evaluate the effects of these ever-growing materials on the microbial structures involved in the OFMSW treatment and the possible relationship between microorganisms and bioplastics.